Bioavailability study of dronabinol oral solution versus dronabinol capsules in healthy volunteers - Parikh N (Dove Medical Press, 2016)
Neha Parikh,1 William G Kramer,2 Varun Khurana,1 Christina Cognata Smith,1 Santosh Vetticaden,1 1INSYS Therapeutics, Inc., Chandler, AZ, USA; 2Kramer Consulting LLC, North Potomac, MD, USA Background: Dronabinol, a pharmaceutical Δ-9-tetrahydrocannabinol, was originally developed as an oral capsule. This study evaluated the bioavailability of a new formulation, dronabinol oral solution, versus a dronabinol capsule formulation. Methods: In an open-label, four-period, single-dose, crossover study, healthy volunteers were randomly assigned to one of two treatment sequences (T-R-T-R and R-T-R-T; T = dronabinol 4.25 mg oral solution and R = dronabinol 5 mg capsule) under fasted conditions, with a minimum 7-day washout period between doses. Analyses were performed on venous blood samples drawn 15 minutes to 48 hours postdose, and dronabinol concentrations were assayed by liquid chromatography–tandem mass spectrometry. Results: Fifty-one of 52 individuals had pharmacokinetic data for analysis. The 90% confidence interval of the geometric mean ratio (oral solution/capsule) for dronabinol was within the 80%–125% bioequivalence range for area under the plasma concentration–time curve (AUC) from time zero to last measurable concentration (AUC0–t) and AUC from time zero to infinity (AUC0–∞). Maximum plasma concentration was also bioequivalent for the two dronabinol formulations. Intraindividual variability in AUC0–∞ was >60% lower for dronabinol oral solution 4.25 mg versus dronabinol capsule 5 mg. Plasma dronabinol concentrations were detected within 15 minutes postdose in 100% of patients when receiving oral solution and in <25% of patients when receiving capsules. Conclusion: Single-dose dronabinol oral solution 4.25 mg was bioequivalent to dronabinol capsule 5 mg under fasted conditions. Dronabinol oral solution formulation may provide an easy-to-swallow administration option with lower intraindividual variability as well as more rapid absorption versus dronabinol capsules. Keywords: pharmacokinetics, Δ-9-tetrahydrocannabinol, safety, variability